TMA for all: a new method for the construction of tissue microarrays without recipient paraffin block using custom-built needles - Andreiuolo Felipe; Pires Andréa; de Souza Simone (BMC, 2006)
Abstract Background TMAs are becoming a useful tool for research and quality control methods, mostly for immunohistochemistry and in situ hybridization. Methods A new technique that allows building TMA blocks with more than 300 tissue cores without using a recipient paraffin block for the tissue cores and without using a commercial TMA builder instrument is described. This technique is based on the construction of TMA needles modifying conventional hypodermic needles to punch tissue cores from donor blocks, which are attached by double-side adhesive tape on a computer-generated paper grid used to align the cores on the block mould, which is filled with liquid paraffin. Results More than two hundred TMA blocks were constructed using this method, utilized in immunohistochemistry and histochemistry as positive and negative controls and also in research. Conclusion This technique has the following advantages: it is easy to reproduce, affordable, quick and creates uniform blocks with more than 300 cores aligned, adherent and easy to cut, with negligible losses during cutting and immunohistochemistry and in situ hybridization procedures.